Identification of CDPKs involved in TaNOX7 mediated ROS production in wheat - Hu, Chun-Hong; Li, Bin-Bin; Chen, Peng; Shen, Hai-Yan; Xi, Wei-Gang; Zhang, Yi; Yue, Zong-Hao; Wang, Hong-Xing; Ma, Ke-Shi; Li, Li-Li; Chen, Kun-Ming (Frontiers in Plant Science, 2023)
As the critical sensors and decoders of calcium signal, calcium-dependent protein kinase (CDPK) has become the focus of current research, especially in plants. However, few resources are available on the properties and functions of CDPK gene family in Triticum aestivum (TaCDPK). Here, a total of 79 CDPK genes were identified in the wheat genome. These TaCDPKs could be classified into four subgroups on phylogenesis, while they may be classified into two subgroups based on their tissue and organ-spatiotemporal expression profiles or three subgroups according to their induced expression patterns. The analysis on the signal network relationships and interactions of TaCDPKs and NADPH (reduced nicotinamide adenine dinucleotide phosphate oxidases, NOXs), the key producers for reactive oxygen species (ROS), showed that there are complicated cross-talks between these two family proteins. Further experiments demonstrate that, two members of TaCDPKs, TaCDPK2/4, can interact with TaNOX7, an important member of wheat NOXs, and enhanced the TaNOX7-mediated ROS production. All the results suggest that TaCDPKs are highly expressed in wheat with distinct tissue or organ-specificity and stress-inducible diversity, and play vital roles in plant development and response to biotic and abiotic stresses by directly interacting with TaNOXs for ROS production.